DEVELOPING STRATEGIC LEARNING COMPETENCIES: EQUIPPING STUDENTS FOR SUCCESSFUL LANGUAGE LEARNING - Sopari, Sopari (Transpublika Publisher, 2023)
Developing students' cognitive and communicative skills is crucial for their success in language learning. This paper explores the role of strategic learning competencies in enhancing language learners' abilities. The paper examines the pertinence of teaching strategic learning skills at the postgraduate level, highlighting the perspectives of both students and instructors. Additionally, it discusses the benefits of incorporating social cognitive learning strategies to support students' language development and communicative competence. This study conducted a literature review to investigate the development of strategic learning competencies in language learners. The review explored how the cultivation of strategic learning skills can empower students to take an active role in their language acquisition and ultimately achieve greater proficiency.